Dampak Usaha Peternakan Ayam Terhadap Kehidupan Masyarakat di Kelurahan Mlilir Perspektif Etika Bisnis Islam - Nafia Kusumandari; Aji Damanuri (Niqosiya: Journal of Economics and Business Research, 2024)
Chicken farming plays a role in improving the welfare of local communities in rural areas. Through a local economic development approach, chicken farming can create jobs, increase income, and contribute to regional economic growth. Business ethics is also related to norms in business activities, including establishing livestock pens. The distance between the settlement and the pen must be considered because it is related to air pollution and other environmental problems that can arise from livestock activities. This research aims to analyze the economic, environmental, and sociological impacts of poultry farming from the perspective of Islamic business ethics. The type of research used is field research using a qualitative descriptive approach. Data collection techniques used include observation, interviews, and documentation. The research results show that chicken farming has an economic impact by creating jobs and increasing people's income. However, there are negative impacts on the environment, such as air pollution, which shows an imbalance in applying business ethics principles. Apart from that, the low motivation of people to raise livestock shows a lack of social responsibility in ensuring social benefits for the surrounding community.